Forge - Anderson, Laurie Halse (2012)
Separated from his friend Isabel after their daring escape from slavery, fifteen-year-old Curzon serves as a free man in the Continental Army at Valley Forge until he and Isabel are thrown together again, as slaves once more.
Sequel to: Chains.
Contains reading group guide and sample of Chains.
Includes bibliographical references.
ages 10 and up
Keywords: Soldiers -- Juvenile fiction; African Americans -- Juvenile fiction; Freed persons -- Juvenile fiction; Slavery -- Juvenile fiction; Soldiers -- Fiction; African Americans -- Fiction; Freedmen -- Fiction; Slavery -- Fiction; Soldiers -- Juvenile fiction; African Americans -- Juvenile fiction; Freedmen -- Juvenile fiction; Slavery -- Juvenile fiction; Pennsylvania -- History -- Revolution, 1775-1783 -- Juvenile fiction; History; Juvenile works; Young adult fiction